Ångstrom‐Scale Silver Particles as a Promising Agent for Low‐Toxicity Broad‐Spectrum Potent Anticancer Therapy. (27th February 2019) - Wang, Zhen‐Xing; Chen, Chun‐Yuan; Wang, Yang; Li, Fu‐Xing‐Zi; Huang, Jie; Luo, Zhong‐Wei; Rao, Shan‐Shan; Tan, Yi‐Juan; Liu, Yi‐Wei; Yin, Hao; Wang, Yi‐Yi; He, Ze‐Hui; et al.
Abstract: Cancer incidence is rising, and the efficacy of current available anticancer agents is limited by severe dose‐limiting toxicities and drug resistance problems. Nanoparticles are heralded as the next frontier in cancer treatment. Here, a pure physical method is used to efficiently fabricate very small silver particles even approaching the Ångstrom (Ång) dimension. Fructose is used as a dispersant and stabilizer to coat the Ång‐scale silver particles (AgÅPs). Functional and mechanistic studies demonstrate that fructose‐coated AgÅPs (F‐AgÅPs) can enter and accumulate in multiple cultured cancer cell lines to induce apoptotic death, whereas most normal cells are resistant to the efficacious dose of F‐AgÅPs; in vivo, intravenous administration of F‐AgÅPs potently inhibits the growth of pancreatic and lung cancer xenografts in nude mice, without inducing notable toxic effects on the healthy tissues. The results suggest the promising potential of F‐AgÅPs as a potent, safe, and broad‐spectrum agent for the cancer treatment. Abstract : Physical method‐fabricated fructose‐coated Ångstrom‐scale silver particles (F‐AgÅPs) have the ability to enter multiple cancer cells to induce apoptosis. Intravenous injection of F‐AgÅPs potently inhibits the growth of cancer xenograft models, without inducing notable toxic effects on healthy tissues. These results suggest that F‐AgÅPs have a great potential to be used as a potent, safe, and broad‐spectrum agent for cancer treatment.